Do approaches to learning affect academic performance of business ethics students? - Mohd Redza, Zaza Eliza; Ismail, Suhaiza; Mhd. Sarif, Suhaimi; Ismail, Yusof (Penerbit UTHM, 2013)
The objectives of this study are to explore the approaches to learning Business Ethics course adopted by students and to examine the relationship between learning approaches and academic performances of Business Ethics course. A questionnaire survey was administered to 209 students taking Business Ethics course in a higher learning institution in Malaysia. The Approaches and Study Skills Inventory for Students (ASSIST) was used to assess the learning approaches adopted by students, whilst the study used Final Examination to measure students’ academic performance. The results indicate that majority students, both male and female groups prefer to use deep approach in studying Business Ethics. The findings also reveal that there are significant positive relationships between deep and strategic approaches and academic performance. On the other hand, there is a significant negative relationship between surface approach and examination result. This study provide guidance to educators to adopt effective teaching strategies to improve student learning by encouraging the right approaches to learning in order to improve students’ academic performance. Keywords: learning approaches, academic performance, ASSIST, gender, ethical judgment